Perfil epidemiológico de doença meningocócica nas capitais da região Centro-Oeste do Brasil - Carvalho Guerini, Amanda (2022)
Introduction: Meningococcal disease is an infectious condition caused by Neisseria meningitidis. The condition has three presentations: Meningococcal Meningitis (MM), Meningococcemia (MCC) and both MM+MCC. In this context, the prognosis without proper diagnosis and treatment can be severe or even fatal. Objectives: Thus, it is essential to discuss the epidemiological profile of this disease in Brazilian cities in the Brazilian Midwest. Material and Methods: This is a cross-sectional, descriptive, and quantitative epidemiological study of cases reported in the capitals of the Brazilian Midwest region between 2016 and 2020 obtained through DATASUS. Prevalence, presentation, sex, age group, and clinical outcomes were the studied variables. Results: During the period, 164 cases were registered in the cities of Brasília, Campo Grande, Cuiabá, and Goiânia, with an annual average of 32.8 cases. The most common form was meningococcal meningitis. Overall, there was an increase in the number of cases between 2016 and 2017, followed by a slight drop until 2019. In 2020, there was an abrupt drop in reported cases, which is a possible repercussion of the COVID-19 pandemic. Conclusion: In short, there is a characteristic distribution of the disease in each city, and adequate sanitary, educational, and medical care measures are instruments to reduce the morbidity and mortality of the meningococcal disease.